Enhanced heat transfer mechanism of nanofluid MQL cooling grinding - Li, Changhe, 1966-; Ali, Hafiz Muhammad, 1981- (IGI Global, 2020)
""This book examines the distribution of airflow field in the grinding zone in nanofluid minimum quantity lubrication cooling grinding; tribological performance in grinding wheel/work piece interface; thermodynamic mechanism in grinding wheel/work piece interface; and surface integrity evaluation"--Provided by publisher"-- Provided by publisher.
Keywords: Grinding wheels.; Lubrication and lubricants.; Nanofluids.; elektronické knihy; electronic books